Prototipe Sistem Absensi Berbasis Web Dan Mobile Dengan Metode Rapid Aplication Development (Rad) - Fried Sinlae; Samidi (Prosiding SISFOTEK, 2021)
Web and Mobile-Based Attendance System Design at PT. Bintang Millennium Perkasa, the author tries to do research to design a web-based information system for PT. Mighty Millennium Star. The main problem of this research is the difficulty of calculating food and transportation fees because there is no real-time recording of attendance. The system development method uses RAD and ISO 9126 testing and system security testing tools with Acunetix, Loic tools, and Hoic tools. By using the Research Methodology Rapid Application Development (RAD). The author's goal is to create an information system that makes it easier for the Human Resources Management (HRD) section to manage employee administration to the company, as a tool for the HRD section and employees to carry out employee administrative processes for the company. As well as displaying employee data, leave and attendance on this website. The result of this research is a Web and Mobile-based attendance system with the main modules are employee data, leave management, and attendance management. The test results with ISO 9126 are good and the acunetix test results are good, Loic is good, Xoic is also good. So it can be concluded that the resulting value still shows the feasibility of the system to be implemented in accordance with the real system in the design of the Human Resource Management information system web and the administrative management of employees towards the company.